2022
DOI: 10.2147/ijwh.s380159
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Unknown Predictors of Maternal Anemia Among Tribal Lactating Mothers, Andhra Pradesh, India: A Prospective Cohort Study

Abstract: Introduction Anemia is a serious public health issue in India, especially among women, adolescent girls, and young children. Tribal people reside mostly in remote underserved regions with little or no basic civic amenities which makes them a highly vulnerable group of Indians. The study aimed to identify unknown risk factors for anemia among tribal lactating mothers. Methodology It was a mixed method prospective cohort study for 10 months carried out among 340 scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have revealed that anaemia prevalence is not uniform among lactating and non-lactating mothers 21 22. Lactating mothers are considered a more vulnerable group than non-lactating mothers as they are physiologically and nutritionally at a higher risk of iron deficiency and could acquire anaemia during their pregnancy 23 24.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that anaemia prevalence is not uniform among lactating and non-lactating mothers 21 22. Lactating mothers are considered a more vulnerable group than non-lactating mothers as they are physiologically and nutritionally at a higher risk of iron deficiency and could acquire anaemia during their pregnancy 23 24.…”
Section: Introductionmentioning
confidence: 99%
“…We could find only a few studies that had assessed the dietary intake of micro-nutrients after pregnancy 8 10 and among them only one had assessed the adequacy of multiple B-group vitamins in Lactating mothers. 7 Study done by Aparicio et al in Spain among lactating mothers showed that around 60% of participants had adequate intake of all the B group vitamins except Folic acid (39%). 8 This might be because Spain being a developed country and the participants don’t belong to any vulnerable group.…”
Section: Discussionmentioning
confidence: 97%
“…Five clusters were randomly selected in the urban and rural areas each from the above list. 7 The project has been approved by All India Institute of Medical Sciences Mangalagiri ethics committee [AIIMS/MG/IEC/2021-22/105].…”
Section: Methodsmentioning
confidence: 99%
“…Indigenous foods are still integral to their sustenance, with a predominantly plant-based diet marked by notable anti-nutritional factors that hinder nutrient absorption and bioavailability. Due to financial constraints, even non-vegetarian tribal populations find it arduous to include animal products in their diets, despite the fact that animal-source foods are consumed in limited quantities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%